1980
DOI: 10.1002/ajim.4700010204
|View full text |Cite
|
Sign up to set email alerts
|

Occupational lead exposure, nephropathy, and renal cancer

Abstract: A 48-year-old lead worker was found to have a cystic renal carcinoma during an evaluation of his occupational lead poisoning. Clinical studies showed elevated blood lead levels, impaired urinary concentrating ability, and reduced creatinine clearance. Histologic and electron microscopic studies showed this cystic tumor to be similar to renal carcinomas observed in animals with prolonged lead exposure. Lead content of the tumor was elevated (2.49 micrograms/gm) in comparison with adjacent renal tissue and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 17 publications
(8 reference statements)
2
17
0
1
Order By: Relevance
“…This accumulation has been shown to compromise some ability of bone cells to respond to hormones and also may result in alterations in the plasma levels of 1,25-dihydroxy-vitamin D 3 (Goyer, 1993;Pounds et al, 1991). Long-term exposure to Pb 2+ may also result in a nephropathy or renal adenocarcinoma (Baker et al, 1980;Buchet et al, 1980;Cooper et al, 1985;Fowler, 1993;Lilis, 1981;Goyer, 1982Goyer, , 1993Selevan et al, 1985).…”
Section: Leadmentioning
confidence: 99%
“…This accumulation has been shown to compromise some ability of bone cells to respond to hormones and also may result in alterations in the plasma levels of 1,25-dihydroxy-vitamin D 3 (Goyer, 1993;Pounds et al, 1991). Long-term exposure to Pb 2+ may also result in a nephropathy or renal adenocarcinoma (Baker et al, 1980;Buchet et al, 1980;Cooper et al, 1985;Fowler, 1993;Lilis, 1981;Goyer, 1982Goyer, , 1993Selevan et al, 1985).…”
Section: Leadmentioning
confidence: 99%
“…However, a similar relationship between nephropathy in workers with occupational exposure to lead and renal cancer has not been clearly established from epidemiological studies, although two case reports have been published (60,61). The potential carcinogenesis of lead has been reviewed recently by EPA because ofthe uncertainty ofthis relationship (62).…”
Section: Nephrotoxicity and Carcinogenesis Lead Nephropathymentioning
confidence: 99%
“…Such tumors have been produced in experimental animals by near-lethal doses of lead (6,7,8,28,40,44,45,46,51,52,53). There are reports (5,22) describing single cases of renal cancer in long-term smelter workers. Selevan et al (41) found six renal cancer deaths where 2.94 were expected in a cohort of 1 987 male smelter workers in Idaho.…”
Section: Renal Cancermentioning
confidence: 99%